Chemical ligation of the influenza M2 protein for solid‐state NMR characterization of the cytoplasmic domain. (27th May 2015) - Kwon, Byungsu; Tietze, Daniel; White, Paul B.; Liao, Shu Y.; Hong, Mei
Abstract: Solid‐state NMR‐based structure determination of membrane proteins and large protein complexes faces the challenge of limited spectral resolution when the proteins are uniformly 13 C‐labeled. A strategy to meet this challenge is chemical ligation combined with site‐specific or segmental labeling. While chemical ligation has been adopted in NMR studies of water‐soluble proteins, it has not been demonstrated for membrane proteins. Here we show chemical ligation of the influenza M2 protein, which contains a transmembrane (TM) domain and two extra‐membrane domains. The cytoplasmic domain, which contains an amphipathic helix (AH) and a cytoplasmic tail, is important for regulating virus assembly, virus budding, and the proton channel activity. A recent study of uniformly 13 C‐labeled full‐length M2 by spectral simulation suggested that the cytoplasmic tail is unstructured. To further test this hypothesis, we conducted native chemical ligation of the TM segment and part of the cytoplasmic domain. Solid‐phase peptide synthesis of the two segments allowed several residues to be labeled in each segment. The post‐AH cytoplasmic residues exhibit random‐coil chemical shifts, low bond order parameters, and a surface‐bound location, thus indicating that this domain is a dynamic random coil on the membrane surface. Interestingly, the protein spectra are similar between a model membrane and a virus‐mimetic membrane, indicating that the structure and dynamics of the post‐AH segment is insensitive to the lipid composition. This chemical ligation approach is generally applicable to medium‐sized membrane proteins to provide site‐specific structural constraints, which complement the information obtained from uniformly 13 C, 15 N‐labeled proteins.